(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background. Polychlorinated biphenyls (PCBs) have been recognized as human carcinogens and cause liver cancer in animal experimental studies. However, no study investigated their association with hepatocellular carcinoma (HCC) so far. This study aimed to evaluate the serum PCB concentration in HCC patients and in healthy subjects of the general population living in Brescia, North Italy, a highly industrialized area with heavy PCB environmental pollution due to the presence of a PCB producing factory. Methods. Lipid-adjusted PCB concentrations, computed as the sum of 24 congeners, were measured in the serum of 101 HCC patients and in 101 healthy subjects of the same age and gender. Results. Hepatitis B and C virus infection and history of heavy alcohol intake were found, alone and combined, in 87% of HCC patients. No difference was found in PCB serum concentration of HCC patients with and without, and according to, the major risk factors for liver disease. No significant difference was observed in serum total PCB concentration between HCC patients (median: 1081; range: 287.0-3182.0 ng/g lipid) and healthy subjects (median: 1199.3; range: 225.7-22825 ng/g lipid). PCB congeners 118, 138, 153, 156, 180 and 194 were the only ones found over the detection limit in at least 30% of HCC patients. The serum level of PCB 118, but not that of other congeners, was higher in HCC patients than in healthy subjects. Conclusion. These findings do not support the hypothesis that PCBs play an important role in HCC development, although a contribution by some specific congeners cannot be ruled out